TEOSQ factorial exploration of youth Brazilian soccer players - Hirota, Vinicius Barroso; Verardi, Carlos Eduardo Lopes [UNESP]; De Marco, Ademir (My University, 2017)
The aim of this research was test the Task and Ego Orientation in Sport Questionnaire, performing the translation, adaptation, reliability and exploratory factor analysis in 540 youth Brazilian´s, male, soccer players (13.56±0.98 age). As a quantitative research, we applied the TEOSQ, and LSSPCI, following six steps: 1. Judgment of Referees; 2. Trial Undergraduates; 3. Pilot Study; 4. Instrument Implementation; 5. Concurrent Validation; 6. Test-retest. Reliability (Cronbach's Alpha coefficient), and exploratory factor analysis (rotated matrix-Varimax and Kaiser Normalization), over the descriptive analysis as statistical. The results shows Alpha´s of 0.81 and 0.82 respectively to ego and task orientation; the factors analysis extracted two factors, in which the issues 01, 03, 04, 06, 09 and 11, has a high load factor related to the component 1, connected to ego, and issues 02, 05, 07, 08, 10, 12 and 13, are related to task orientation indicating that all the saturation values were above 0.40 for each factor. The average were 4.22 for task orientation and 2.39 for ego, most of the younger athletes are task oriented demonstrating a significant correlation among the orientations. We conclude that the instrument exhibits good stability and its internal factors relate in for each goal´s orientation, and can be replicated across soccer players.
Keywords: Achievement motivation; Evaluation; Goals orientation; Soccer; Youth players